Decoding optical communication based on cell phone cameras - Gu, Zixuan (Nanyang Technological University, 2023)
This report introduces a novel approach to decode visible light communication (VLC) using a smartphone camera. The proposed scheme employs a smartphone as a receiver to capture continuous light state variations, which remain imperceptible to the naked eye. Information conveyed in the form of alternating light and dark stripes is seized by the camera, subsequently decoded by the smartphone. This research emphasizes the utilization of MATLAB for the design of an algorithm proficient in decoding these light and dark stripe data, aiming for enhanced accuracy. Then, this report also proposes a new demodulation scheme design algorithm aimed at augmenting the demodulation efficiency. This innovative method provides a new perspective in the field of visible light communication, opening avenues for efficient and user-friendly VLC decoding techniques.